PERANCANGAN SISTEM INFORMASI PSIKOTES ONLINE DALAM SELEKSI DAN REKRUITMEN KARYAWAN MENGGUNAKAN METODE EXTREME PROGRAMING BERBASIS WEB (STUDI KASUS : PTC PERTAMINA) - chalifah istifadha; Maulana Ardhiansyah (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
The development of information technology As users of smartphones, internet, laptops and so on, we have been made familiar with information and communication technology. PT Pertamina Training & Consulting (PTC) is a subsidiary of PT PERTAMINA (PERSERO) which focuses on developing human resources through services, consulting and human resource management. PTC Pertamina employee candidate acceptance still uses forms, candidate registration takes 10 to 30 minutes to fill out the form. HRD staff need 10 to 15 minutes to find candidate data for the next stage using a paper form, so HRD staff re-enters in Microsoft Excel to find out the psychological test test results. In designing this employee recruitment, the method used is the Extreme programming (XP) method, which is to analyze and build a system using cycles or processes that are sequentially in developing an information system. The results of this study are online psychological tests in employee selection and recruitment with the aim of facilitate HRD staff in searching for candidate data management, managing Pertamina PTC psychological test candidate data based on the Extreme Programming Method procedure. And can facilitate employees and HRD staff in inputting psychological test results and the identity of prospective PTC Pertamina employees.